Purple Urinary Bag Syndrome (PUBS) in Benign Prostate Hyperplasia (BPH) with long-term indwelling urinary catheter use: a case report and literature review - Made Kresna Yudhistira Wiratma; Putu Dewi Octavia; Eric Sebastian Hutauruk (DiscoverSys Inc., 2020)
Background: PUBS is one of the clinical manifestations of urinary tract infection. This condition often leads patients, patients’ families, and medical workers to worrisome. Metabolism of tryptophan and infection of sulfatase and phosphatase - producing bacteria is the most acceptable pathogenesis explaining PUBS. Many risk factors are underlying this condition, including long-term use of indwelling urinary catheters, constipation, dementia, chronic kidney disease, and bedridden patients. This case study aims to evaluate the recent treatment of supporting factors in treating the underlying urinary infection.Case Presentation: We presented a case report of a 67year-old man with Benign Prostate Hyperplasia (BPH) and long-term use of indwelling urinary catheter who complained of purple discoloration of urine a day prior to Transurethral Resection of the Prostate (TURP) surgery. The patient complained of no fever and pain while urinating and having no history of the same complaint and other diseases. In addition, the patient has diagnosed with BPH and Urinary Tract Infection. The administration of Cefazolin 2 grams dosage was given before the TURP procedure, and the following procedure continued.Conclusion: PUBS is a rare clinical course alarming the urinary tract infection. Appropriate treatment by Cefazolin 2 grams dosage following by TURP shows a favorable outcome in this case study.